Influência das condições ergonômicas do trabalho na produtividade da mão de obra na execução do serviço de armação - Carvalho, Laísa Cristina (2020)
Civil construction is one of the activities that generates more jobs in the country, however it still has traditional construction methods, but also with great technological advancement. The number of workers in this area is quite significant, due to the diversity of activities existing in a building. In the case of the reinforcing steel service, tasks are performed manually and request different degrees of effort, which when applied recursively, with tools and equipment unsuitable and inadequate workplace, may cause damage to the health and comfort of workers. In this context, this study aims to relate the ergonomic conditions of the workplace with the productivity of the workforce in the execution of the reinforcing steel service, establishing a cause-effect relationship. Thus, the conduct of this research is based on a field survey in the execution of the reinforcing steel service in 37 construction sites, with the achievement of labor productivity indicators and ergonomic work evaluation based on three ergonomic analysis instruments (Ergonomic Workplace Analysis - EWA, Metabolic Equivalent - MET and Occupational Repetitive Actions - OCRA) and statistical analysis on which ergonomic conditions influence labor productivity, as well as their intensity of influence. The originality of this thesis consists in the establishment of the statistical relationship between the ergonomic conditions detected and the productivity of the labor force in the execution of the beam, column reinforcement service. According to the statistical analysis applied to the sample, the ergonomic conditions resulting from the application of MET and OCRA instruments were found to influence labor productivity, while this influence was not detected statistically through the application of the EWA instrument. As contributions, in addition to establishing an equation for predicting labor productivity based on the ergonomic conditions detected through the application of the ergonomic assessment instruments MET and OCRA, the statistical procedure adopted can also be highlighted, which can be generalized for studies of a similar nature considering other activities of the reinforcing steel service or even other services.